Synchronization analysis for stochastic multi-layer networks: Event-based impulsive control with predefined impulsive intervals - Liu, Hengyu; Li, Jiarong; Jiang, Haijun; Wang, Jinling; Hu, Cheng (Nonlinear Analysis: Modelling and Control, 2025)
This article explores the novel approach to addressing the intra/inter-layer synchronization challenges in stochastic multi-layer networks (SMLNs). First, considering the influence of time delay in control, an event-triggered delayed impulsive control (ETDIC) strategy is developed, where the impulsive instant is determined by the predesigned event-triggered mechanism. Moreover, by introducing piecewise auxiliary functions, it effectively excludes Zeno behavior within the ETDIC framework. The study then derives sufficient conditions for ensuring intra- and inter-layer; synchronization, leveraging the Lyapunov method and rigorous mathematical analysis. Finally, theoretical results are validated through numerical simulations.